2016
DOI: 10.18632/oncotarget.10250
|View full text |Cite
|
Sign up to set email alerts
|

LINC00052 regulates the expression of NTRK3 by miR-128 and miR-485-3p to strengthen HCC cells invasion and migration

Abstract: Long non-coding RNAs (LncRNAs) are a group of RNAs that are more than 200 nt in length but cannot encode proteins. Accumulating evidences showed that abnormal LncRNA expressions are highly involved in many kinds of tumor. By using gene trap methods which could knockdown gene expression to find important genes, we found one LncRNA which called intergenic non-protein coding RNA 52 (LINC00052) has the ability to inhibit invasion and migration of hepatocarcinoma cells. We found that invasion, migration and prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 29 publications
1
61
1
Order By: Relevance
“…A noncoding small RNA is also called as microRNA (miRNA), which generally includes about 20 nucleotides and has the ability to modulate some target genes . In recent years, several miRNAs have been clarified in human diseases, and some existing researches have implied that miRNAs were correlated with the development of HCC, such as miR‐128, miR‐485‐3p, and miR‐221 . As one of the miRNAs, miR‐124‐3p belongs to the miR‐124 family, and was proved to be related with different kinds of human diseases, including nasopharyngeal carcinoma, gastric cancer, and glioblastoma .…”
Section: Introductionmentioning
confidence: 99%
“…A noncoding small RNA is also called as microRNA (miRNA), which generally includes about 20 nucleotides and has the ability to modulate some target genes . In recent years, several miRNAs have been clarified in human diseases, and some existing researches have implied that miRNAs were correlated with the development of HCC, such as miR‐128, miR‐485‐3p, and miR‐221 . As one of the miRNAs, miR‐124‐3p belongs to the miR‐124 family, and was proved to be related with different kinds of human diseases, including nasopharyngeal carcinoma, gastric cancer, and glioblastoma .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that lncRNAs could modulate the biological behaviors of HCC cells through their neighboring mRNAs [15,19]. The neighboring mRNA of CRNDE was IRX5 (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Accumulating evidence showed that lncRNA might be a competing ceRNA or a molecular sponge in inflecting the expression and biological functions of miRNA [15]. Using a bioinformatics databases (Starbase, RNAhybrid), miR-136-5P is a putative target of CRNDE in several miRNAs (Table 2).…”
Section: Reciprocal Repression Between Crnde and Mir-136-5pmentioning
confidence: 99%
“…The function of LINC00052 varies depending on the location of tumors. It acts as a tumor suppressor through inhibiting cell proliferation, invasion and migration in hepatocellular carcinoma (Xiong et al 2016;Yan et al 2018;Zhu et al 2017), whereas it could promote breast cancer growth (Salameh et al 2017) and gastric cell metastasis and proliferation (Shan et al 2017).…”
Section: Discussionmentioning
confidence: 99%